Taboo Words In “The Monkey” Movie ( Sociolinguistic Approach) - Setiawan, Ade; Effendi, Dedi; Magria, Vera (Universitas Muara Bungo, 2025)
The researcher analyzes taboo words that uttered by some characters in the monkey movie use sociolinguistic approach. The purpose of this research are to analyze and explain types of taboo word and the function of taboo word. In analyzing the data, the researcher using descriptive qualitative research purposed by Endaswara (2013). The data are gained through non-participant method. The sources of the data are the monkey movie and its transcript. The data are collected by selecting dialogues containing taboo word after watching the video and matching the transcript with subtitle of the movie with carefully. The researcher gets the data is formed by word and phrase that refers to taboo word. The data are presented through formal and informal method and using table for data presented. The result of this research are stated as follows. The first, four types of taboo words occur in the characters utterance in the monkey movie. There are epithet, profanity, vulgarity, and obscenity. From 17 data that found in the movie, epithet are the most appearing type in this movie with nominal data : 7 data ephitet, 5 data profanity, 3 data obscenity, 2 data vulgarity. While for the function the researcher only found there from four types. And the strongest function that appear on this movie is to show contempt. With nominal 12 data refers to to show contempt, 3 data refers to draw attention and 3 data refers to be propocative